Intersubtype differences in the effect of a rare p24 Gag mutation on HIV-1 replicative fitness - Chopera, Denis R.; Cotton, Laura A.; Zawaira, Alexander; Mann, Jaclyn K.; Ngandu, Nobubelo K.; Ntale, Roman; Carlson, Jonathan M.; Mlisana, Koleka; Woodman, Zenda; Rosa, Debra de Assis; Martin, Eric; Miura, Toshiyuki; et al. (Journal of Virology, 2012)
Certain immune-driven mutations in HIV-1, such as those arising in p24Gag, decrease viral replicative capacity. However, inter-subtype differences in the replicative consequences of such mutations have not been explored. In HIV-1 subtype B, the p24Gag M250I mutation is a rare variant (0.6%) that is enriched among elite controllers (7.2%) (p=0.0005) and appears to be a rare escape variant selected by HLA-B58 supertype alleles (p<0.01). By contrast, in subtype C, it is a relatively common minor polymorphic variant (10-15%) whose appearance is not associated with a particular HLA allele. Using site-directed mutant viruses, we demonstrate that M250I reduces in vitro viral replicative capacity in both subtype B and subtype C sequences. However, whereas in subtype C downstream compensatory mutations at p24Gag codons 252 and 260 reduce the adverse effects of M250I, fitness costs in subtype B appear difficult to restore. Indeed, patient-derived subtype B sequences harboring M250I exhibited in vitro replicative defects while those from subtype C did not. The structural implications of M250I were predicted by protein modeling to be greater in subtype B versus C, providing a potential explanation for its lower frequency and enhanced replicative defects in subtype B. In addition to accounting for genetic differences between HIV-1 subtypes, the design of CTL-based vaccines may need to account for differential effects of host-driven viral evolution on viral fitness.